Photocatalytic degradation of sulfamonomethoxine in aqueous phase using PW12/TiO2 composites under UV lights. (October 2018) - Wan, T; Cheng, W; Shi, W J; Ren, J H; Wu, W; Yao, J
Abstract: A composite catalyst with phosphotungstic acid and TiO2 has been synthesized by sol-gel method. The phase, structure, morphology and optical properties were explored by the X-ray diffraction (XRD), electron microscopy (SEM) and ultraviolet-visible diffuse reflectance (UV-Vis DRS). The effects of calcilation temperature, calcilation time and the doping ratio of phosphotungstic acid on the catalytic performance of the composite catalyst were investigated for sulfamonomethoxine (SMM) degradation. Results showed that the TiO2 in the sample had an anatase type and had a large specific surface area and a better catalytic performance when compared with the pure TiO2 . When Recycling tests with calcination temperature of 500 degree centigrade, calcination time of 2h and PW12 /TiO2 doping ratio of 0.35, the degradation of SMM in water phase was high by photo catalytic treatment of PW12 /TiO2 composites under UV lights. With UV radiation for 30 min, the degradation efficiency of SMM can up to 90% and the synthesized catalyst had a high recovery.